Pregnancy continuation and organizational religious activity following prenatal diagnosis of a lethal fetal defect are associated with improved psychological outcome†. (26th May 2015) - Cope, Heidi; Garrett, Melanie E.; Gregory, Simon; Ashley‐Koch, Allison
Abstract Objective The aim of the article is to examine the psychological impact, specifically symptoms of grief, post‐traumatic stress and depression, in women and men who either terminated or continued a pregnancy following prenatal diagnosis of a lethal fetal defect. Method This project investigated a diagnostically homogeneous group composed of 158 women and 109 men who lost a pregnancy to anencephaly, a lethal neural tube defect. Participants completed the Perinatal Grief Scale, Impact of Event Scale – Revised and Beck Depression Inventory‐II, which measure symptoms of grief, post‐traumatic stress and depression, respectively. Demographics, religiosity and pregnancy choices were also collected. Gender‐specific analysis of variance was performed for instrument total scores and subscales. Results Women who terminated reported significantly more despair (p = 0.02), avoidance (p = 0.008) and depression (p = 0.04) than women who continued the pregnancy. Organizational religious activity was associated with a reduction in grief (Perinatal Grief Scale subscales) in both women (p = 0.02, p = 0.04 and p = 0.03) and men (p = 0.047). Conclusion There appears to be a psychological benefit to women to continue the pregnancy following a lethal fetal diagnosis. Following a lethal fetal diagnosis, the risks and benefits, including psychological effects, of termination and continuation of pregnancy should be discussed in detail with an effort to be as nondirective as possible. © 2015 John Wiley & Sons, Ltd.